1, 3, 5‐Tri(iodoethynyl)‐2, 4, 6‐trifluorobenzene: halogen‐bonded frameworks and NMR spectroscopic analysis. Issue 2 (1st April 2017) - Szell, Patrick M. J.; Gabidullin, Bulat; Bryce, David L.
Abstract : Single‐crystal X‐ray diffraction structures are reported for a series of seven halogen‐bonded cocrystals featuring 1, 3, 5‐tris(iodoethynyl)‐2, 4, 6‐trifluorobenzene as the halogen‐bond donor, and bromide ions (as ammonium or phosphonium salts) as the halogen‐bond acceptors. Detailed NMR analyses (in solution and in the solid state) of this halogen‐bond donor are also presented. Abstract : Halogen bonding is the non‐covalent interaction between the region of positive electrostatic potential associated with a covalently bonded halogen atom, named the σ‐hole, and a Lewis base. Single‐crystal X‐ray diffraction structures are reported for a series of seven halogen‐bonded cocrystals featuring 1, 3, 5‐tris(iodoethynyl)‐2, 4, 6‐trifluorobenzene (1) as the halogen‐bond donor, and bromide ions (as ammonium or phosphonium salts) as the halogen‐bond acceptors: (1)·MePh3 PBr, (1)·EtPh3 PBr, (1)·acetonyl‐Ph3 PBr, (1)·Ph4 PBr, (1)·[bis(4‐fluorophenyl)methyl]triphenylphosphonium bromide, and two new polymorphs of (1)·Et3 BuNBr. The cocrystals all feature moderately strong iodine–bromide halogen bonds. The crystal structure of pure [bis(4‐fluorophenyl)methyl]triphenylphosphonium bromide is also reported. The results of a crystal engineering strategy of varying the size of the counter‐cation are explored, and the features of the resulting framework materials are discussed. Given the potential utility of (1) in future crystal engineering applications, detailed NMR analyses (in solution and in the solid state) of this halogen‐bond donor are also presented. In solution, complex 13 C and 19 F multiplets are explained by considering the delicate interplay between various J couplings and subtle isotope shifts. In the solid state, the formation of (1)·Et3 BuNBr is shown through significant 13 C chemical shift changes relative to pure solid 1, 3, 5‐tris(iodoethynyl)‐2, 4, 6‐trifluorobenzene.